النهج التربوي في تعليم وتعلم اللغة الإنجليزية نحو تحسين جودة التعليم - عبدالجليل Mona Salem Ali (مجلة الاصالة, 2025)
The study aims to investigate the pedagogical approach in teaching and learning towards improved quality education, the importance of using pedagogical approaches in teaching and learning process, the contributions of pedagogical approaches in teaching and learning trends in the academic performance of students, and innovative pedagogical approaches in teaching and learning effectiveness in the educational setting. Mixed methods are utilized through Focus Group Discussion in the pedagogical approach in teaching and learning towards improved quality education. The study comprised sixty (60) respondents only. Results show that pedagogical approach to teaching and learning towards improved quality education encompasses the educational system and multiple pedagogies in stemming the various philosophy of learning based on global approach, show that importance of using pedagogical approaches in teaching and learning process is considered as the significant factors in the learning process, wisdom, and invaluable knowledge to achieve quality education, show that contributions of pedagogical approaches in teaching and learning trends in the academic performance of students create a culture and responsibility through class participation and directed teachers’ instructions in the process and complexity of pedagogical approach in the educational system, and show that innovative pedagogical approaches for teaching and learning effectiveness in the educational setting increases the demand and effort of students in fostering the growth and accelerated needs perspectives in the academic achievement and output to the fullest.